2000
DOI: 10.1161/01.cir.102.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Bosentan, an Endothelin Receptor Antagonist, in Patients With Pulmonary Hypertension

Abstract: Background-Few treatments are available for isolated pulmonary hypertension (PHT), which has a high morbidity and mortality. This trial was designed to assess the hemodynamic effects of bosentan, an endothelin receptor antagonist, in patients with PHT, in which local overproduction of endothelin-1 (ET-1) is thought to play a pathogenic role. Methods and Results-An open-label, dose-ranging study was performed in 7 female patients with primary PHT (nϭ5) or isolated PHT associated with limited scleroderma (nϭ2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(92 citation statements)
references
References 42 publications
3
85
0
4
Order By: Relevance
“…Its first reported use was in 7 female patients, 5 with primary pulmonary hypertension and 2 with pulmonary hypertension associated with scleroderma in an open-label dose-ranging study. 30 Bosentan infused intravenously in 50-, 150-, and 300-mg doses at 2-hour intervals produced a dose-dependent fall in pulmonary artery pressure and pulmonary vascular resistance and a slight increase in cardiac index. The trial, however, was prematurely terminated when 2 of the 7 patients died within 36 hours of entering the second part of the study.…”
Section: Pulmonary Hypertensionmentioning
confidence: 98%
“…Its first reported use was in 7 female patients, 5 with primary pulmonary hypertension and 2 with pulmonary hypertension associated with scleroderma in an open-label dose-ranging study. 30 Bosentan infused intravenously in 50-, 150-, and 300-mg doses at 2-hour intervals produced a dose-dependent fall in pulmonary artery pressure and pulmonary vascular resistance and a slight increase in cardiac index. The trial, however, was prematurely terminated when 2 of the 7 patients died within 36 hours of entering the second part of the study.…”
Section: Pulmonary Hypertensionmentioning
confidence: 98%
“…15,16,60 In clinic, efficacy and safety of endothelin-receptor antagonist has been confirmed in PAH patients. [61][62][63][64] Because ET-1 (upregulated in PAH) activates NFATc1, which in turn increases bcl ¡ 2 expression, contributing to the prosurvival and antiapoptotic effects of ET-1, 65 endothelin-receptor antagonist might also inhibit NFAT activation. At present, most of studies found that interventions targeting NFAT pathway may be effective for PAH therapy.…”
Section: Targeting the Nfat Pathway For Pah Therapymentioning
confidence: 99%
“…Another group of substances that are currently being introduced in the treatment of pulmonary hypertension, are endothelin antagonists [50]. Plasma endothelin levels are increased in patients with systemic sclerosis but the association of increased endothelin levels and pulmonary hypertension is unclear [51].…”
Section: Treatmentmentioning
confidence: 99%
“…Plasma endothelin levels are increased in patients with systemic sclerosis but the association of increased endothelin levels and pulmonary hypertension is unclear [51]. Based on preliminary experiences in patients with PPH, these substances offer a promising perspective especially in conjunction with prostanoids [50]. A recently completed randomized, placebo-controlled multicentre trial showed that the dual endothelin receptor antagonist bosentan improves exercise capacity, pulmonary arterial pressure and cardiac output in patients with PPH and PAH associated with CREST/scleroderma [52].…”
Section: Treatmentmentioning
confidence: 99%